2017
DOI: 10.19173/irrodl.v18i4.3025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating NTU’s OpenCourseWare Project with Google Analytics: User Characteristics, Course Preferences, and Usage Patterns

Abstract: <p class="3">As freely adoptable digital resources, OpenCourseWare (OCW) have become a prominent form of Open Educational Resources (OER). More than 275 institutions in the worldwide OCW consortium have committed to creating free access open course materials. Despite the resources and efforts to create OCW worldwide, little understanding of its use exists. This paper reports OCW project development at National Taiwan University (NTU) and investigates its use with Google Analytics. Reports include strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…They also reported that several factors should be considered when using social media within MOOCs, such as the required number of posts and the balance between leisure and learning time. Sheu and Shih [41] highlighted the successful implementation of the open courseware project at National Taiwan University (NTU). Specifically, 26 new courses are added each year, and over 100 faculty members have actively participated in this project.…”
Section: Usagementioning
confidence: 99%
“…They also reported that several factors should be considered when using social media within MOOCs, such as the required number of posts and the balance between leisure and learning time. Sheu and Shih [41] highlighted the successful implementation of the open courseware project at National Taiwan University (NTU). Specifically, 26 new courses are added each year, and over 100 faculty members have actively participated in this project.…”
Section: Usagementioning
confidence: 99%
“…There are serious problems that occur in developing countries in Asia such as Indonesia; one of which is that there are still digital gaps, especially for teachers, this is, of course, a separate challenge that must be overcome through various ways by involving all relevant stakeholders. However, a study by Sheu and Shih (2017) statistically shows the successful use of OCW at National Taiwan University, specifically for the lecture materials which are overall designed for Chinese users who live in urban areas, where information and communication technology is more developed. The research concludes that accessibility needs to be continuously developed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Taiwan there is Opensource OCW Prototype System (OOPS), formed by an organization consisting of volunteers (Lee et al, 2007), headquartered in Taiwan. It was originally designed to translate open source materials from the MIT OCW site into Chinese (Sheu & Shih, 2017). The success of the CW movement in China is largely due to initiatives from the Chinese government who provide special incentives for developers of lecture materials to be distributed openly.…”
Section: Ocw Movement In Chinamentioning
confidence: 99%
See 2 more Smart Citations